New biologically active sulfonamides as potential drugs for Alzheimer's disease - Nevyhoštěná, Marie; Komersová, Alena; Pejchal, Vladimír; Štěpánková, Šárka; Česla, Petr; Matzick, Kevin; Macháčková, Jana; Svoboda, Roman (Archiv der Pharmazie, 2024)
A family of new compounds with sulfonamide and amide functional groups as potential Alzheimer's disease drugs were prepared by multistep synthesis. Thermal stability measurements recorded the initial decomposition in the range of 200-220°C, close above the melting point. The final compounds were tested for their ability to inhibit acetylcholinesterase and butyrylcholinesterase, and the in vitro dissolution behavior of selected compounds was studied through both lipophilic and hydrophilic matrix tablets. All nine tested derivatives were even more active in inhibiting acetylcholinesterase than the clinically used rivastigmine. Regression analysis of the obtained dissolution profiles was performed, and the effects of the pH and the release mechanism were determined. Some substances showed remarkable biological activity and became a subject of interest for further extensive study.
Keywords: Alzheimer's disease; rivastigmin; Acetylcholinesterase; Butyrylcholinesterase; cholinesterasové inhibitory; acetylcholinesterasa; butyrylcholinesterasa; koncentrace vodíkových iontů; Cholinesterase Inhibitors; Rivastigmine; Alzheimer Disease; sulfonamidy; synthesis; sulfonamides; Sulfonamides; vztahy mezi strukturou a aktivitou; Humans; Hydrogen-Ion Concentration; dissolution testing; molekulární struktura; Alzheimerova nemoc; cholinesterase inhibitors; Solubility; Structure-Activity Relationship; rozpustnost; lidé; Molecular Structure